2016
DOI: 10.1186/s12862-016-0838-2
|View full text |Cite
|
Sign up to set email alerts
|

Are sexually selected traits affected by a poor environment early in life?

Abstract: BackgroundChallenging conditions experienced early in life, such as a restricted diet, can detrimentally affect key life-history traits. Individuals can reduce these costs by delaying their sexual maturation, albeit at the price of the later onset of breeding, to eventually reach the same adult size as individuals that grow up in a benevolent environment. Delayed maturation can, however, still lead to other detrimental morphological and physiological changes that become apparent later in adulthood (e.g. shorte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 113 publications
(121 reference statements)
1
19
0
Order By: Relevance
“…In our study, once nutritional stress was alleviated (all animals on normal-diet), we found that as animals increased their growth rates, there was no concomitant reduction in immunocompetence. This lack of a trade-off between investment in compensatory growth and investment into immune function is in contrast to results in damselflies (Stoks et al, 2006) and poultry (van der Most et al, 2011), but is in accordance with work conducted on zebra finches (Killpack et al, 2014). In garter snakes , measures of adaptive but not innate immune function have been shown to trade off with reproduction.…”
Section: Trade-offs With Physiologysupporting
confidence: 81%
See 2 more Smart Citations
“…In our study, once nutritional stress was alleviated (all animals on normal-diet), we found that as animals increased their growth rates, there was no concomitant reduction in immunocompetence. This lack of a trade-off between investment in compensatory growth and investment into immune function is in contrast to results in damselflies (Stoks et al, 2006) and poultry (van der Most et al, 2011), but is in accordance with work conducted on zebra finches (Killpack et al, 2014). In garter snakes , measures of adaptive but not innate immune function have been shown to trade off with reproduction.…”
Section: Trade-offs With Physiologysupporting
confidence: 81%
“…Animals deploy different strategies to mitigate early-life nutritional stress on growth and maturation (Auer, 2010;Mueller et al, 2012;Vega-Trejo et al, 2016). Growth rates are plastic, particularly in species with indeterminate growth, and are usually regulated at optimal rather than maximal rates (Arendt, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, our models included 'days since maturity', as previous studies have shown that it can influence both sperm number and velocity (e.g. Vega-Trejo et al, 2016). However, we excluded this term from our final models as it had no effect.…”
Section: Discussionmentioning
confidence: 99%
“…A high-quality developmental environment is generally predicted to confer lasting benefits on individual performance [3]; this is known as the "silver-spoon" effect [4]. For instance, high quality environments in early life can lead to increased survival [5,6], fecundity [7], mating success [8][9][10], sperm quality and quantity [8,11,12], and immune function [13,14] in adulthood, compared to individuals from poor environments.…”
Section: Introductionmentioning
confidence: 99%